A Study of Conspicuous Consumption in the Chinese Automobile Market - AU, Tai Shan (2007)
Shenzhen (SZ), one the fastest growing province of China, is suffering the problem of excess number of cars in recent years. This problem causes traffic congestion and air-pollution. Many people argue that the problem of excess number of car is caused by conspicuous consumption, which means that people purchase the product not for the utility of products, but for showing off their wealth. Conspicuous consumption has been studied by a number of authors in the past. However, a study of conspicuous consumption of a particular market in a particular country is scarce. This paper aims to study the conspicuous consumption in the Chinese Automobile Market. In addition, qualitative research method and semi-structure interviews are used, in order to understand the reasons of buying luxury vehicles. The participants of this research are car owners and car agents and they have been interviewed. Interview results are analysed and discussed. Finally, recommendations are given to policy makers.